(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
Teacher education for language teaching is based on the premise that teachers can deliver quality education when they are supported with adequate training about updated pedagogies in addressing learner needs and making classrooms socially just and inclusive. In the contemporary world, multilingual education has gained momentum on account of the majority of learners and teachers being multilingual. Based on their diverse pedagogical needs, teachers need to be supported through in-service continuous professional development (CPD) activities with a multilingual turn. This paper critically reviews the state of affairs in Indian language teacher education to make teachers ready for delivering English education in multilingually diverse classrooms. It presents a pertinent discussion on the lack of multilingual CPD activities in Indian language education and teacher training policy. To address this gap, the present paper adopts a narrative overview approach to report two examples from short-term research projects in India that provide evidence of the benefits of adopting a multilingual turn in CPD of in-service Indian teachers. Thereafter, drawing from the positive experiences of the teachers in these projects, it operationalises the multilingual pedagogical needs of Indian teachers which are equally applicable to other multilingual teacher education contexts, globally. It classifies different types of translanguaging which can be practiced in the classroom and presents classroom strategies to be included during multilingual CPD training. It is hoped that such multilingual CPD activities would help teachers cope with the contextual challenges of dealing with linguistically diverse classrooms. It would also help them systematically scaffold instruction to cater to the cognitive and affective needs of their multilingual learners and deliver education in a socially just manner.